Tinjauan Hukum Islam terhadap Perkawinan Beda Kelas Muslim Sasak di Lombok - Basriadi, Basriadi (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2015)
This article attempts to examine in depth, based on the theory of kafÃ¢âah, different class marriages in the Sasak Muslim community, Lombok. The study concludes that on one hand, the different class marriages between noblewomen and non-noblemen do not have an impact on the purpose of marriage which is to create sakÃ®nah, mawaddah, and rahmah household. On the other hand, the marriage that is based on Islamic values is able to realize a happy and harmonious household regardless of social status background. The most important thing in domestic life is communication and trust between husbands and wives. In fiqh munÃ¢kah}Ã¢t, it is required when someone is looking for a spouse, something that needs to be seen is lineage, beauty, wealth and religion. This article would like to emphasize that there is no prohibition in Islam to marry people of different social class.